Maternal care at home for children with special needs - Livian Damiele Coelho Ramos; Juliana Rezende Montenegro Medeiros de Moraes; Liliane Faria da Silva; Fernanda Garcia Bezerra Goés (Universidad de Antioquia, 2015)
Objective.To identify the feasibility of home care and difficulties of mothers who deliver this care for children with special health needs (CRIANES) and to analyze the role of nurses as facilitators of this care. Methods. This descriptive study with a qualitative approach included ten mothers of CRIANES who completed a semi-structured interview at a teaching hospital in the municipality of Rio de Janeiro, Brazil. Data were analyzed using a thematic analysis. Results. Participants pointed out as difficulties the accessibility of treatment facilities and the presence of complex disease. The administration of medicines was classified as both easy and difficult. Features that made home care feasible were help of the child and preparation of nurses in the hospital context for home care. Maternal love helped mothers to overcome difficulties. Conclusion. Encouragement from the nursing team for centered family care is needed. In addition, mothers should be better prepared for the transition from hospital to home. The health network needs to be reorganized with inclusion of CRIANES in the primary care network in order to reduce the dependency of this population on hospitals and to help broaden the social network for CRIANES.